Prospects for a unified Caribbean in the New International Economic order - Venner, K. Dwight (Eastern Caribbean Central Bank BasseterreKN, 1996)
Examines the international system and its role in accommodating even the smallest states in the international community. Focuses on the role of the United Kingdom, Canada, the Caribbean states and in particular, the OECs, in surmounting the barriers to development in this new dispensation.